Manual of Poultry Production in the Tropics - The Technical Centre for Agriculture and Rural Co-Operation; Say R. R. (Wallinford: CAB International, 1987)
The publication of this manual on poultry farming is therefore well-timed. It is a handy guide to all aspects of poultry farming in the tropics. The book includes a thorough study of the anatomy and physiology of poultry as well as information on how to choose strains and produce hybrids. Considering the damage caused by epidemics such as Newcastle disease which is capable of wiping out whole flocks of birds in a few days or even hours, the section on diseases looks at prevention and treatment, including hygiene and vaccination programmes. A table of the main microbial infections with the causes, principal symptoms and treatments, is a special bonus. In poultry keeping as in other enterprises, good management is crucial. The final chapters of this book therefore give detailed advice on how to manage a poultry farm. There is also a section on rearing guinea fowl and ducks, which includes a part on integrated duck/fish production. This book is written in textbook style with clear illustrations and is suitable for agricultural students and extension workers as well as those directly involved in tropical poultry farming.
uaa 22/01/19
Loans
Keywords: Poultry; Livestock production; Agriculture